Sistem Pemantauan Penggunaan Listrik Rumah Tangga Dengan Website Berbasis IoT - Ridwan, Ridwan; Mulia, Sandy Bhawana; Rosid, Achmad Ibnu (Journal of Energy and Electrical Engineering, 2023)
Electricity, as a very important source of energy, was distributed to customers in the amount of 245518.17 GWh in 2019, and 42.25% of customers were households. The high consumption of electricity needs to be kept in mind. It is necessary to have a good and intelligent energy efficiency system. Nowadays, Internet of Things (IoT) technology is being widely used. The electricity monitoring system and prediction of the use of electrical energy in real time based on technology can be one solution to the problem of electrical energy efficiency. For this reason, the Monitoring System for household electricity use using an Internet of Things-based website is expected to increase user awareness and make electrical energy efficient in household groups. This study designs Internet of Things (IoT) technology for a smart monitoring system in everyday electricity use. The research method is experimental with a quantitative approach. This study tries Firebase as an IoT platform with NodeMCU ESP-32 as the microcontroller. The sensor used to detect all electrical parameters is PZEM 004T V3. Monitoring data in real time can be accessed via a web browser. The system as a whole system works well, in accordance with the desired work design. The average value of error reading energy is 2% or a difference of 0.01 kWh every day, as well as latency testing with an average delay of 21.5 ms, with 64 Byte data testing with a timeout of 1000 ms, 0.2% packet loss percentage of 548 data